Health and social care devolution: the Greater Manchester experiment. (22nd March 2016) - Walshe, Kieran; Coleman, Anna; McDonald, Ruth; Lorne, Colin; Munford, Luke
Abstract : Although we know that the aims of devolution are to improve health and reduce health inequalities, it is less clear how this will be achieved. Kieran Walshe and colleagues examine how it might work and the likely problems